Everyone loves live music a theory of performance institutions - Holt, Fabian 1972- (The University of Chicago Press, 2020)
Introduction. The Social Study of Musical Performance Institutions -- Conceptualizing Musical Performance Culture Clubs in Everyday Urban Life -- The Social Study of Music in Cities -- The Commercial Institutionalization of Rock Clubs in New York -- How Did Institutionalization Evolve in Europe? : Music Festivals in the Summer Season -- A Worldview History of Music Festivals -- The Evolution of Anglophone Global Culture -- Three Industry Evolutions That Changed Festival Culture -- New Media, New Festival Worlds
Includes bibliographical references and index
Keywords: Live-Auftritt; Festival; Sozialer Wandel; Rockmusik; Konzert -- Veranstaltung; Rock music / Social aspects / United States; Rock music / Social aspects / Europe; Music festivals / Social aspects / United States; Music festivals / Social aspects / Europe